Determinants of condom use status among men who have sex with men (MSM) group in 5 Indonesian cities in 2015 - Ni Wayan Putri Larassita Parwangsa; Krisnawati Bantas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Significant increase in HIV cases among men who have sex with men (hereafter MSM) group during the 2015-2016 period confirmed that sexual behavior is a major risk factor in exposure to HIV & AIDS with unprotected sexual intercourse as the dominant risk factor. This study aims to identify the determinants of condom use status among MSM group in 5 cities in Indonesia.Methods: This study used a cross sectional design, carried out in 5 cities in Indonesia: Jakarta, Bandung, Semarang, Surabaya, and Denpasar using secondary data from the Integrated Biological and Behavioural Survey (IBBS) in 2015.Results: Variables that are significantly related to the condom use status were marital status, exposure to information on HIV&AIDS, and knowledge about condoms. The marital status variable has a POR value of 1.351 (95% CI OR 0.709 í¢AS 2.576), whilst exposure to HIV&AIDS information has 1.668 (95% CI OR 1.148 í¢AS 2.422) POR value, and knowledge about condoms has POR value as much as 1.925 (95% CI OR 1.274 í¢AS 2.907).Conclusion: The number of respondents who used condoms consistently for the past one month were 76.1% and those who did not were 23.9%. Variables that are significantly related to the behaviour of not using condoms are marital status, exposure to HIV&AIDS information, and knowledge of condoms. Keywords: Determinants, Behavior, Condom, MSM, HIV&AIDS Received: 12 March 2019; Reviewed: 16 April 2019; Revised: 26 April 2019; Accepted: 30 June 2019 DOI: 10.35898/ghmj-32544